2011
DOI: 10.1159/000330034
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Bystander Stress Alters Brain, Behavior, and the Epigenome of Developing Rat Offspring

Abstract: The prenatal environment, including prenatal stress, has been extensively studied in laboratory animals and humans. However, studies of the prenatal environment usually directly stress pregnant females, but stress may come ‘indirectly’, through stress to a cage-mate. The current study used indirect prenatal bystander stress and investigated the effects on the gross morphology, pre-weaning behavior, and epigenome of rat offspring. Pregnant Long-Evans rats were housed with another female rat that underwent eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 79 publications
0
24
0
1
Order By: Relevance
“…Studies need to be conducted to determine what effects changes to postnatal maternal care alone have on the epigenome, in order to assert that these changes are unrelated to the prenatal stress paradigm. Therefore, because prenatal stress has previously been associated with gene expression changes in the brain [19,20,43,51], and the prenatal period is characterized by extreme plasticity, we believe the changes we identified in gene expression were likely induced by the exposure to prenatal stress. …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies need to be conducted to determine what effects changes to postnatal maternal care alone have on the epigenome, in order to assert that these changes are unrelated to the prenatal stress paradigm. Therefore, because prenatal stress has previously been associated with gene expression changes in the brain [19,20,43,51], and the prenatal period is characterized by extreme plasticity, we believe the changes we identified in gene expression were likely induced by the exposure to prenatal stress. …”
Section: Discussionmentioning
confidence: 89%
“…The plethora of epigenetic changes support fetal programming and developmental plasticity theories confirming offspring change in response to the prenatal environment. Future studies should look to further correlate the epigenetic changes to behavioural and neuroanatomical outcomes, such as those in our earlier studies [11,19,20]. We recognize the study is limited by the possibility that the prenatal stress paradigm altered maternal care, and the altered maternal care was responsible for the genetic changes identified.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It appears, however, that early stress can be quite subtle. Mychasiuk et al (46) housed two pregnant dams together throughout their pregnancies. One dam was given mild prenatal stress as in the earlier studies, whereas the other dam was not.…”
Section: Factors Influencing Prefrontal Developmentmentioning
confidence: 99%
“…Numerous studies within our lab have examined the effects of gestational stress on these specific brain areas (Mychasiuk et al, 2011aMuhammad et al, 2012). Recently, we found that PPS significantly influenced early behavior, and had a significant effect on DNA global methylation levels in the prefrontal cortex (PFC) (Mychasiuk et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 99%